2022
DOI: 10.3389/fphar.2022.1022627
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the “gene–protein–metabolite” network of coronary heart disease with phlegm and blood stasis syndrome by integrated multi-omics strategy

Abstract: Background: According to the theory of traditional Chinese medicine, phlegm and blood stasis (PBS) is the pathological basis for coronary heart disease (CHD). This study aimed to explore the biological basis of PBS syndrome in CHD.Methods: Using a strategy that integrated RNA-seq, DIA-based proteomics, and untargeted metabolomics on 90 clinic samples, we constructed a “gene–protein–metabolite” network for CHD-PBS syndrome. We expanded the sample size and validated the differential genes and metabolites in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…17,18 Investigations indicate that PDT causes alteration in the expression of PTGS2. 19 The co-expression of PTGS2, CXCL8, and FOS in coronary heart disease has been investigated and reported by Yang et al 20 Considering the high value of fold change for the FOS gene and its activation by four neighbors, it can be concluded that the hyper-activation of FOS is a key point in the effect of PDT. CXCL8 is upregulated extremely, and similar to FOS, it is activated by three neighbors.…”
Section: Discussionmentioning
confidence: 98%
“…17,18 Investigations indicate that PDT causes alteration in the expression of PTGS2. 19 The co-expression of PTGS2, CXCL8, and FOS in coronary heart disease has been investigated and reported by Yang et al 20 Considering the high value of fold change for the FOS gene and its activation by four neighbors, it can be concluded that the hyper-activation of FOS is a key point in the effect of PDT. CXCL8 is upregulated extremely, and similar to FOS, it is activated by three neighbors.…”
Section: Discussionmentioning
confidence: 98%
“…Considering the abundant features embedded in omics data, it is possible to infer diverse relationships, especially those among micro-level elements, including cells, genes and proteins. In recent years, a large amount of omics data related to TCM have been accumulated, including bulk transcriptomics [ 40 , 41 ], metabolomics [ 42 , 43 ] as well as single-cell omics [ 44–46 ] related to specific herbs and/or TCM syndromes ( Figure 2 ). From a data perspective, computational methods related to mining network relationships from omics data are similar for both TCM and Western medicine.…”
Section: Methodologies Of Tcm-npmentioning
confidence: 99%
“…[ 60 ] established a CPN, providing a basis for personalized diagnosis and treatment of TCM. From a micro perspective, we can achieve the integration of disease diagnosis and syndrome differentiation by performing relevant gene prediction or omics data analysis based on the disease phenotypes and syndrome characteristics, followed by the construction of similarity metrics and correlation analysis based on biological molecular networks [ 40 , 42 , 65 , 91–93 , 94 ]. For example, mining the relationships between Cold/Hot syndromes and neuro-endocrine-immune (NEI) biological networks [ 91 ], analyzing the biological basis of spleen deficiency syndrome and its relationships with digestive diseases [ 92 ], analyzing the biological basis of PBS syndrome in coronary heart disease (CHD) and establishing diagnostic markers to achieve ‘same disease with different treatments’ [ 42 ].…”
Section: Methodologies Of Tcm-npmentioning
confidence: 99%
“…To enable the analysis and interpretation of the generated multidimensional data, the development of improved omics data integration and analysis tools is crucial. Typically, differential genes, proteins, and metabolites are generated routinely and then integrated into the gene-protein-metabolite network using the MetaboAnalyst database and the String database [122]. This method is called a multistage approach with an initial emphasis.…”
Section: Tools For Integrating Omics Datamentioning
confidence: 99%